The Effect of Work Facilities, Work Space Layout, and Team Building on Employee Performance - Rizky Maulana Fadillah; Andriya Risdwiyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to identify the influence of work facilities, workspace layout, and team building on employee performance. Using descriptive quantitative research methods, this study involved employees from two companies: PT Borobudur, Prambanan, and Ratu Boko Temple Tourism Park and PT Naisha Inspirasi Muslimah Yogyakarta. The sample consisted of 80 people, with 40 employees from each company. Data were collected through questionnaires distributed in the form of a paper survey. Analyses were conducted using Statistical Product and Service Solutions (SPSS) version 23.0 to test validity, reliability, multicollinearity, basic assumptions, and multiple linear regression. The research findings show that (1) work facilities have a positive and significant effect on employee performance, (2) work layout has a negative and insignificant effect, (3) team building has a positive and significant effect, and (4) the three variables simultaneously have a significant effect on employee performance.